1988
DOI: 10.1172/jci113682
|View full text |Cite
|
Sign up to set email alerts
|

Serum prostacyclin stabilizing factor is identical to apolipoprotein A-I (Apo A-I). A novel function of Apo A-I.

Abstract: Serum PGI2 stabilizing factor (PSF) was purified from human serum to a single protein with a molecular weight of 28,000 D by SDS-PAGE. Analyses of NH2-terminal sequence (32 residues), COOH-terminal sequence (3 residues) and the composition of amino acids disclosed its homology with human apolipoprotein A-I (Apo A-I), a major apolipoprotein of HDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(66 citation statements)
references
References 26 publications
5
60
0
1
Order By: Relevance
“…Possible explanations include the fact that HDL-C has antioxidant and antiinflammatory properties (6, 7), attenuates endothelial dysfunction (8,9), has anticoagulant effects (10,11), and enhances the half-life of prostacyclin (12)(13)(14). The antiinflammatory properties of HDL-C may be particularly relevant here, because we observed systemic inflammation and endothelial activation in patients with PAH with low HDL-C levels (Table 8).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Possible explanations include the fact that HDL-C has antioxidant and antiinflammatory properties (6, 7), attenuates endothelial dysfunction (8,9), has anticoagulant effects (10,11), and enhances the half-life of prostacyclin (12)(13)(14). The antiinflammatory properties of HDL-C may be particularly relevant here, because we observed systemic inflammation and endothelial activation in patients with PAH with low HDL-C levels (Table 8).…”
Section: Discussionmentioning
confidence: 84%
“…High-density lipoprotein cholesterol (HDL-C) is associated with a lower risk of coronary heart disease (4,5).The underlying mechanisms behind this protective effect include stimulation of reverse cholesterol transport, antioxidant and antiinflammatory properties (6,7), attenuation of endothelial dysfunction (8,9), anticoagulant effects (10,11), and enhancement of prostacyclin half-life (12)(13)(14). Interestingly, except for reverse cholesterol transport, derangements in all of these mechanisms have been implicated in the pathobiology of PAH.…”
mentioning
confidence: 99%
“…It also promotes an increased hydrolysis of cholesterol esters in smooth muscle cells, allowing the release of cholesterol to HDL-A1. Experiments have shown [116] that HDL-A1 prolongs the half-life of PGI2 from 5 minutes to 22 minutes. These authors showed that apo-A1 bound to HDL forms a complex with PGI2, thus delaying its degradation, and therefore promoting vasodilation and platelet stability.…”
Section: A Proposed Role For the Atheromamentioning
confidence: 99%
“…Because of its alpha-helix structure it can bind to PGI2 which is originally an unstable substance and causes PGI2 stabilization thereby imparting an important protective anti-aggregatory effect against platelet thrombi formation at sites of vascular damage. Thus it contributes towards its novel anti atherogenic function of prevention of coronary artery disease [3].…”
Section: Introductionmentioning
confidence: 99%